Safeguarding CRISPR-Cas9 gene drives in yeast - DiCarlo, James E. (Nat Biotechnol, 2015)
RNA-guided gene drives capable of spreading genomic alterations made in laboratory organisms through wild populations in an inheritable way could be used to control populations of organisms that cause environmental and public health problems. However, the possibility of unintended genome editing through the escape of strains from laboratories, coupled with the prospect of unanticipated ecological change, demands caution. We report the efficacy of CRISPR-Cas9 gene drive systems in wild and laboratory strains of the yeast Saccharomyces cerevisiae. Furthermore, we address concerns surrounding accidental genome editing by developing and validating methods of molecular confinement that minimize the risk of unwanted genome editing. We also present a drive system capable of overwriting the changes introduced by an earlier gene drive. These molecular safeguards should enable the development of safe CRISPR gene drives for diverse organisms.